First steps sorting and opposites - Clark, Lesley; Hind, Garie Photographer; Ladybird Books Ltd. (Loughborough, England Ladybird Books Ltd., 1997)
Designed to introduce children to the idea that things can be categorized into sets and groups. This book features photographs of everyday objects, with each spread illustrating an opposite. The text encourages children to talk about sorting the objects into groups.
Includes photographs of everyday objects illustrating sorting and opposites concepts
Preschool children
Keywords: Sorting-Opposites-Concept Learning-Early childhood education